Acceptability, feasibility and preliminary impact evaluation of a pilot text‐message study on improving the health of Aboriginal people with, or at risk of, chronic disease in Australia. Issue 1 (23rd November 2022) - Waller, Karen; Furber, Susan; Bauman, Adrian
Abstract: Issue addressed: Aboriginal people experience higher rates of chronic disease than other Australians, largely due to modifiable risk factors. This study aimed to evaluate the acceptability, feasibility and preliminary impact of a pilot text‐message program on improving the health of Aboriginal people with, or at risk of, chronic disease. Methods: A before and after study using a convenience sample of Aboriginal Australian adults determined the impact of a 6‐month healthy lifestyle text‐message intervention on lifestyle behavioural measures including nutrition, physical activity and smoking. Process evaluation of participants and program facilitators determined program acceptability and feasibility. Results: Twenty Aboriginal people enrolled in the study, with high study completion and program acceptability. The two program facilitators reported the low‐cost automated text‐message program to be highly acceptable, feasible to deliver and led to environmental program changes. Preliminary impact data showed significant improvements in vegetable consumption at 3 and 6 months, but not for other health outcome measures. Conclusions: The text‐message program was highly acceptable and feasible to deliver, and has potential as an adjunct to usual care. Further research is required to determine program efficacy with a larger sample size. So what?: Text‐messages to improve the health of Aboriginal people are highly acceptable, feasible to deliver and can complement existing community‐led group programs. Further testing of this low‐cost program is warranted to determine program efficacy.